PENERAPAN PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) SEBAGAI UPAYA MENINGKATKAN KREATIVITAS MATEMATIKA SISWA KELAS X SMAN ANGKOLA SELATAN - Susi Sulastri Lubis (Universitas Muhammadiyah Tapanuli Selatan, 2018)
Mathematics requires some aspects to support the learning process, including the ability of creativity. It is necessary to look for an alternative learning activity that can enhance learning and provide opportunities for students more active. A cooperative learning approach to the type of the Think-Pair-Share (TPS) is one of the alternatives to increase the liveliness of students in learning mathematics; math is creativity, so students increased. This research is a study of a class act in SMAN Angkola South, with the subject population, is a whole grade X-A SMAN Angkola South, as the object of research, is the ability of teachers to manage learning and student activities in the implementation of learning and ability of students in the student's creativity through the implementation of cooperative approaches type TPS. From the results, it can be concluded that the application of the cooperative learning model types Think-Pair-Share (TPS) can be used to enhance the ability of creativity mathematics students. The results of the evaluation at the end of the cycle I indicate the average score reached 34.16 class with the completeness of classical learning percentage of 30%. In cycle II, the average class reached 77.16 by the rate of completeness of classical learning of 90%. Thus the increase in the percentage of completeness of classical learning of 60%. Keywords: Think-Pair-Share, the ability to understand the concept of